Estimating the Burden of Illness Related to Genital Warts in Russia: A Cross-Sectional Study - Vera N. Prilepskaya; Mikhail Gomberg; Smita Kothari; Karen Yee; Amit Kulkarni; Suzanne M. Garland; Anna R. Giuliano (Journal of Health Economics and Outcomes Research)
**Background:** Human papillomavirus (HPV) infections are the etiologic agents of genital warts (GW). HPV is one of the most frequent sexually transmitted viral infections, and nearly 65% of individuals with partners who have GW also develop GW. In Russia, as in many other countries, overall GW prevalence data are scarce. Given the lack of Russian data, our study estimated GW prevalence in physician practices and GW-related health care resource use in Russia among male and female patients aged 18–60 years.